CREATIVE APPROACHES TO INCREASE SPIRITUAL AND EDUCATIONAL ACTIVITIES OF FUTURE TEACHERS - Zokirjonov , Abbosbek Zokirjon o‘g‘li (Educational Research in Universal Sciences, 2023)
This article provides information on appropriate use of methods and recommendations of creative approaches to spiritual-educational activity among future teachers. Also, effective methods of forming a system of spiritual and educational activity in future teachers have been revealed.